2022
DOI: 10.1111/1365-2664.14204
|View full text |Cite
|
Sign up to set email alerts
|

Spatial aggregation of herbivores and predators enhances tri‐trophic cascades in paddy fields: Rice monoculture versus rice‐fish co‐culture

Abstract: Rice‐fish co‐culture system has a history of more than 2,000 years in Asia and has been recognized as one of FAO's Globally Important Agricultural Heritage Systems (GIAHS). To date, few studies have explored rice‐fish co‐culture effects on the relationship between predator–prey aggregations and associated tri‐trophic cascades of predatory spiders, insect herbivores and rice. Indeed, predators have been shown to increase prey spatial aggregation but it is still not clear how fish (tertiary consumers) affect agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Quantitative synthesis of global data across agroecosystems, forests, marine, grasslands, and wetlands has proven that plant genetic diversity influences plant performance by lowering pressure from antagonists across trophic levels of different plants (Wan, Cavalieri, et al, 2022). Similarly, meta-analysis studies have indicated that the abundance of plant species promotes pest regulatory services by enhancing predator and parasitoid abundance, predation, and parasitism (Wan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative synthesis of global data across agroecosystems, forests, marine, grasslands, and wetlands has proven that plant genetic diversity influences plant performance by lowering pressure from antagonists across trophic levels of different plants (Wan, Cavalieri, et al, 2022). Similarly, meta-analysis studies have indicated that the abundance of plant species promotes pest regulatory services by enhancing predator and parasitoid abundance, predation, and parasitism (Wan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that interspecific competition is seldom sufficient to exclude competitors-despite all stemborer species occurring inside the stem lumen. This paradox may be explained by a high level of aggression, intraguild predation, and cannibalism [71,73,178] that reduce intraspecific competition and limit interspecific encounters inside the rice plant [231]; and by the intraspecific aggregation of egg masses and larvae in the rice crop [134,232,233] Oligophagy plays a large role in stemborer species' coexistence (Figure 4). Crop plants offer a highly favorable resource for most herbivores because of their high nutrient content (due to fertilizers), their relatively consistent access to water, and often low anti-herbivore defenses [72,73].…”
Section: Resource Partitioning and Potential Coexistence Mechanismsmentioning
confidence: 99%